FTIR analysis on modified kapok fiber via esterification for Palm Oil Mill Effluent (POME) treatment: article - Hishamuddin, Azleen Haziera; Alias, Nor Halaliza (2017)
Palm oil mill effluent is a waste product from the palm oil industry and it was considered as a drawback to the environment. This effluent was highly polluted and many studies have been conducted in order to determine the most economical and environmental friendly scheme for palm oil mill (POME) treatment. The objectives for this research were to modify the kapok fiber using esterification technique and to analyze the unmodified and modified kapok fiber using Fourier Transform Infrared (FTIR) spectroscopy. The kapok fiber was modified by using esterification reaction with the different percentages of catalyst (5% w/w, 10% w/w and 15% w/w). The modified kapok fiber was analyzed by using Fourier Transform Infrared (FTIR) spectroscopy to observe the functional groups presented after modification and the results were compared with the unmodified kapok fiber. Based on the FTIR spectra, the ester group was formed at the range of 17331737 cm-1 for the esterified kapok fiber for all of the percentages of catalyst. Meanwhile, the alcohol O-H stretching was presented at the region of 3329-3346 cm-1 both for unmodified and modified kapok fiber. However, the alcohol OH stretch in esterified kapok fiber has reduced due to the reaction between the alcohols with stearic acid to form an ester. The best modification was by using the 5% of calcium oxide as the result showed the highest formation of ester which was 90.5%T. In conclusion, it shows that the esterification reaction has successfully modified the characteristic of the unmodified kapok fiber.